2007
DOI: 10.1093/intimm/dxm083
|View full text |Cite
|
Sign up to set email alerts
|

CXCL16 is a novel mediator of the innate immunity of epidermal keratinocytes

Abstract: The epidermis is constantly exposed to a variety of microbial pathogens and plays a vital role in resisting them. Soluble CXC chemokine ligand (CXCL) 16, which is one of the ELR- CXC chemokines, acts as a mediator of innate immunity by attracting CXC chemokine receptor (CXCR) 6-expressing cells, such as activated T cells and NKT cells. However, the production of CXCL16 by non-immune cells remains unclear. We found that cultured keratinocytes produced a significant amount of CXCL16 (2-3 ng per 10(6) cells per 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…35 Also, it was reported that nonimmune cells such as smooth muscle cells and keratinocytes expressed CXCL16. 34,36 In our experiment, we found that CXCL16 was expressed on the damaged glomerular cells, probably mesangial cells, but not on intact glomerular cells, and the development of glomerulopathy recruited NKT cells into affected kidney, where CXCL16 was expressed.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…35 Also, it was reported that nonimmune cells such as smooth muscle cells and keratinocytes expressed CXCL16. 34,36 In our experiment, we found that CXCL16 was expressed on the damaged glomerular cells, probably mesangial cells, but not on intact glomerular cells, and the development of glomerulopathy recruited NKT cells into affected kidney, where CXCL16 was expressed.…”
Section: Discussionmentioning
confidence: 56%
“…19 CXCL16 was discovered as a ligand for CXCR6 that is expressed on activated T and NKT cells and is a membranebound chemokine. 33,34 We hypothesized that renal injury mediated by anti-GBM Ab might induce the intraglomerular upregulation of CXCL16. As shown in Figure 5A, CXCL16 was BASIC RESEARCH www.jasn.org expressed evidently by the induction of ecGN regardless of the presence of NKT cells.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL16 is produced by diverse tissues and cells including dendritic cells (21), lymphocytes (59), vascular smooth muscle cells (55), bone marrow stromal cells (45), tumor cells (40,41), and cardiac tissue (61). Furthermore, SR-PSOX/ CXCL16 is expressed on human endothelial cells and is strongly upregulated by stimulation with proinflammatory cytokines such as TNF-␣ or IFN-␥ (1, 26), mediators associated with inflammatory diseases or ischemia (49,53). Thereby the stimulation of CXCL16 production by TNF-␣ depends on NF-B, p38 MAPK, and protein kinase A (22).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL16 is produced by several cell types including dendritic cells (21), lymphocytes (56), vascular smooth muscle cells (52), bone marrow stromal cells (40), tumor cells (35,36), and cardiac tissue (58). SR-PSOX/CXCL16 expression in endothelial cells is upregulated by proinflammatory cytokines, such as TNF-␣ or IFN-␥ (1,25), known mediators of inflammation and ischemia (46,50). TNF␣ stimulates CXCL16 production via a signaling cascade involving NF-B, p38 MAPK, and protein kinase A (22).…”
Section: Discussionmentioning
confidence: 99%